Global financial crisis and China’s pawnbroking industry - Zhou, Liming; Yao, Shujie; Wang, Jinmin; Ou, Jinghua (Taylor & Francis, 2016)
In most countries, pawnbroking is an intermediate financial instrument to help private households or individuals meet their short-term and urgent consumption needs. In China, due to market imperfection and institutional discrimination against the small and medium-sized enterprises (SMEs) by commercial banks and other formal financial institutions, pawnbroking has been used as a supplementary financing source for SMEs and private entrepreneurs when they cannot get access to bank credits or other financial sources such as usury (underground money shops). This paper uses first-hand survey data in 2009 in Zhejiang Province, China’s pioneering region for pawn business, and secondary data for the whole country during 2004-12, to understand the special characteristics of the pawnbroking industry and explain why it has become a viable and useful financing instrument in China. It also explains the puzzle of a serious setback and widespread losses in the industry during the world financial crisis. A corporate financing model of SMEs is developed to explain the substitution relationship between formal bank credits and pawnbroking. It suggests that the stimulus plan implemented by the central government of China during the global financial crisis reduced the borrowing cost and lowered the access barrier of bank credits to SMEs, leading to a temporary setback of an otherwise rapidly growing pawnbroking business in 2008 and 2009. However, as quantitative easing is gradually phased out after the global financial crisis, pawnbroking activities recover rapidly, implying that the industry will continue to play an important role in China’s economic development given its current financial system which is still unfriendly to the SME sector.